Hypospadias Surgery An Illustrated Textbook - Hadidi, Ahmed T.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This is the second edition of a well-received textbook that reflects the state of the art in Hypospadias Surgery. It provides a comprehensive reference that covers the History, Embryology, Anatomy, Morphology, Pathogenesis, Epidemiology, Genetics, all surgical techniques, their complications and long term follow up of Hypospadias. It is well illustrated with more than 2000 colour illustrations, operative photographs, surgical tips & tricks and complications. Hypospadias Surgery has become a true sub-specialty; however, there is a wide diversity of opinions, and a large number of operations have been described. In this unique volume, a team of world-class authors (42 experts from 19 countries) presents a professional and updated global overview on the management of this condition, highlighting and exploring the current philosophy and the different principles and techniques of hypospadias repair. Pediatric Urologists, Pediatric Surgeons, Plastic Surgeons and Urologists will benefit from reading this Second Edition. This book represents an excellent practical guide not only to surgeons in training, but also to more expert surgeons involved in the management of this common, but troublesome condition. (3z(BSurgeons should not operate on a patient with hypospadias unless they have read, marked, learnt and inwardly digested every word in every chapter in this book(3y(B. (review of the first edition in the European Journal of Plastic Surgery, 2004.s
Section 1. General & Basic Science -- Preface of first and second editions -- 1. History of hypospadias -- 2. Men behind principles and principles behind techniques -- 3. Normal Development of the Penis and Urethra -- 4. Surgical Anatomy of the Penis -- 5. Prepuce: Altered Development in Hypospadias and its Management based on Patho-embryologic Landmarks -- 6. Morphology of hypospadias -- 7. Pathogenesis of hypospadias -- 8. The Urethral Plate and Chordee -- 9. Classification & Assessment of hypospadias -- 10. Epidemology of hypospadias -- 11. Genetic Aspects of Hypospadias -- 12. Hormones and Growth of the Genital Tubercle -- 13. The Role of Preoperative Androgen Stimulation in the Management of Hypospadias -- 14. Timing of Surgery -- 15. General Principles -- 16. Plastic Surgery Principles -- 17. Principles of Hypospadias Surgery -- 18. Analgesia -- Section 2. Surgical Techniques -- 19. Grade I: Glanular Hypospadias Double Y Glanuloplasty (DYG) Technique -- 20. MAGPI and Modified MAGPI -- 21. The Meatal-based Flap Principle -- 22. Slit-Like adjusted Mathieu technique (SLAM) -- 23. Megameatus Intact Prepuce (MIP) Deformity -- 24. Thiersch-Duplay Principle The Glans Approximation Procedure (GAP) -- 25. The Inverted Y Thiersch Technique -- 26. Incision of the Urethral Plate -- 27. Dorsal Inlay TIP (DTIP) -- 28. Urethral Advancement for Treatment of Distal Hypospadias -- 29. Glanular urethral Disassembly (GUD) technique -- 30. Proximal Hypospadias with Small Flat Glans; The Lateral Based Onlay (LABO) Flap Technique -- 31. The Island Onlay Hypospadias Repair -- 32. Perineal Hypospadias The Bilateral Based (BILAB) Skin Flap Technique -- 33. Chordee Excision and Distal Urethroplasty (CEDU) for Perineal Hypospadias -- 34. Preputial Island Flaps -- 35. The modified Asopa (Hodgson XX) procedure to repair hypospadias with chordee -- 36. Koyanagi Technique and its Modifications in Management of Proximal Hypospadias -- 37. The Yoke Hypospadias Repair -- 38. Dorsal Longitudinal Penile Skin Island Flap in One-Stage Repair of Hypospadias with Penoscrotal Transposition -- 39. Grafts for one stage repair -- 40. Two-Stage Graft Urethroplasty Free Full-Thickness Wolfe Graft -- 41. The Cecil Culp Technique -- 42. The Foreskin and Circumcision -- 43. Protective intermediate layer -- 44. Procedures to Improve the Appearance of the Meatus and Glans -- 45. Buried penis -- 46. Penile torsion -- 47. Congenital Urethral Duplication -- 48. Large Prostatic Utricle Associated to Hypospadias -- 49. Penoscrotal Transposition -- 50. Uncommon Conditions and Complications -- 51. Hypospadias surgery in Adults -- 52. Flaps versus Grafts -- 53. Single Stage versus Two Stage Repair -- 54. Stenting versus no stenting -- 55. Dressing versus no dressing -- 56. Editorial Overview of Current Management of Hypospadias -- Section 3. Complications -- 57. Early complications -- 58. Meatal stenosis and urethral stricture -- 59. Functional Urethral obstruction (FUO) -- 60. Hypospadias fistula -- 61. Genital Lichen sclerosus (Balanitis Xerotica Obliterans) A review -- 62. Urethral diverticulae and acquired megalo urethra -- 63. Management of failed hypospadias surgery -- 64. Complex and Redo Hypospadias Repairs: Management of 402 Patients -- Section 4. Long Term results -- 65. Long term consequences of hypospadias repair -- 66. Long term follow up in hypospadias repair: what is it and are we there yet? -- 67. The Story of my Life with Hypospadias -- 68. Tissue Engineering and Future Frontiers -- 69. How to write a paper on hypospadias. -- 70. Hypospadias Centers, Training and Hypospadias Diploma.
Keywords: Surgery; Children$1 (BSurgery.s; Urology; Surgery; Pediatric Surgery; Urology; Hypospadias -- surgery; Hypospadias -- complications; Surgical Procedures, Operative -- methods